Jejak Historis Klenteng Boen Tek Bio Sebagai Cagar Budaya Warisan Etnis Tionghoa di Tangerang - Regina Permatadewi; Tantiany Gunawan (Jurnal Ilmu Pendidikan dan Sosial, 2022)
The journey in the culture of the Ethnic Chinese side brings historical evidence in witnessing their journey. Starting from the architecture, dance, musical instruments, etc. which is passed down from generation to generation. One of them is embedded in the absolute historical testimony of the Chinese Ethnic in Tangerang is contained in the body of the Boen Tek Bio Temple. Basically, between generations who pass down blood ties do not fully understand the importance of a historical trace in the architecture that was established, especially the Boen Tek Bio Temple as a place of worship for the Chinese. This is what makes an implication in historical traces so that they require them to be able to know and introduce the history in the Boen Tek Bio Temple. This also creates history on the side that is not extinct and always gets re-examination in other research innovations. Thus, the Boen Tek Bio Temple is used as a cultural heritage of the ancestral heritage of the Chinese in Tangerang. Apart from being a place of worship, the Boen Tek Bio Temple also keeps a historical imprint that needs to be implanted and passed on by word of mouth and between generations. This is what makes the history of the Boen Tek Bio Temple to be well maintained and implemented as a cultural heritage.